Težave z definicijo pojma ŠPORT - Kristan, Silvo (Šport (Ljubljana), 2024)
Definitions of technical terms are a conditio sine qua non (a necessary, first condition) in every science and in every technical language for a given term to be understood in the same way by everyone. If we do not all understand technical terms equally, any discussion about them is fruitless, pointless. It is futile to communicate using undefined or imprecisely defined concepts, because each discussant understands the concept in their own way. Therefore, the formulation of correct and contextually appropriate definitions of technical terms is one of the most important tasks of any science (M. Uršič, O. Markič: Osnove logike The Basics of Logic, Faculty of Arts, 1997, p. 38).
Keywords: dtrokovni pojmi; strokovni termini; šport